Determination of Total Flavonoid Content in Medicinal Plant Leaves Powder Using Infrared Spectroscopy and Chemometrics - Lestyo Wulandari; Bayu Dwi Permana; Nia Kristiningrum (Universitas Gadjah Mada, 2020)
Flavonoid is phenolic compounds consisting of fifteen carbon atoms and is commonly found in plants. Infrared (IR) spectroscopy combined with chemometrics, has been developed for a simple analysis of flavonoid in the medicinal plant leaves powder. IR spectra of selected medicinal plant powder were correlated with flavonoid content using chemometrics. The chemometric methods used for calibration analysis were Partial Least Square (PLS), Principal Component Regression (PCR), and Support Vector Regression (SVR). After the calibration model was formed, it was then validated using Leave-One-Out-Cross-Validation (LOOCV) and 2-fold cross-validation. In this study, the PLS of the Near-infrared (NIR) calibration model showed the best calibration with R-Square and RMSEC values of 0.9676524 and 0.0978202, respectively. The LOOCV of PLS of the NIR calibration model has the R-square and RMSE values of 0.9850164 and 0.067663, respectively. The 2-fold cross-validation gave the R-square and RMSE values of 0.9857071 and 0.2104665, respectively. PLS of the NIR calibration model was further used to predict unknown flavonoid content in commercial samples. The significance of flavonoid content that has been measured by NIR and UV-Vis spectrophotometry was evaluated with paired samples T-test. The flavonoid content that has been measured with both methods gave no significant difference.